Therapeutic Uses of the Polyherbal Drug Triphala in Geriatric Diseases - DR. MRADU GUPTA (International Journal of Pharma and Bio Sciences, 2010)
Degenerative physiological changes related to old-age are increasing world over. These geriatric diseases affect almost all vital body systems. The rejuvenating and preventive therapy called Rasayana therapy in Ayurvedic system of Indian medicine deals with prevention, amelioration and cure of geriatric ailments by increasing overall body immunity, fighting infections & antigens, and preventing carcinogenic mutations. A specific polyherbal preparation called Triphala, which consists of equal amounts of fruits of three plants namely Terminalia chebula Retz., Terminalia bellirica Roxb. and Emblica officinalis Gaertn. in fine powder form, has been specifically mentioned in traditional Ayurvedic texts for its beneficial effects in geriatric diseases. It contains tannins, phenols and glycosides which are responsible for its strong antioxidant activity apart from its immunomodulatory, anti-inflammatory, analgesic and antimutagenic properties. These attributes make Triphala an effective remedy for geriatric degenerative diseases.